Changes and events over life course: a comparative study between groups of older adults - Luípa Michele Silva; Antônia Oliveira Silva; Luiz Fernando Rangel Tura; Maria Adelaide Silva Paredes Moreira; Jordana Almeida Nogueira; Stefano Cavalli (Universidade de São Paulo, 2015)
OBJECTIVE: to identify the changes which had occurred over the last year in the life of older adults, as well as the values attributed to these changes.METHOD: this is a multicentric, cross-sectional study, of the inquiry type, undertaken in three cities of the Brazilian Northeast, investigating two distinct groups of older adults.RESULTS: among the 236 older adults interviewed, it was observed that 30.0% reported health as the main change in their life course in the last year, this category being the most significant response among the older adults aged between 80 and 84 years old (37.7%). Changes in the family were mentioned by 11.5% of the older adults; death (9.6%) and alterations in routine activities (9.6%). In relation to the value attributed to these changes, it was ascertained that for 64.7% of the older adults aged between 65 and 69 years old, these changes were positive. In the older group, 49.4% of the older adults believe that their changes were related to losses.CONCLUSION: the knowledge of the changes mentioned, the value attributed to these changes, and the self-evaluation of health provide information which assists in formulating actions which are more specific to the real needs of these age groups. They also provide the health professionals with a better understanding of how some experiences are experienced in the life trajectories of these older adults.